Hearing Safety From Single- and Double-Pulse Transcranial Magnetic Stimulation in Children and Young Adults. Issue 4 (July 2017) - Kukke, Sahana N.; Brewer, Carmen C.; Zalewski, Christopher; King, Kelly A.; Damiano, Diane; Alter, Katharine E.; Hallett, Mark
Abstract : Purpose: Concerns regarding hearing safety have limited the number of studies using transcranial magnetic stimulation (TMS) in children and young adults. The objective of this study was to examine the safety of TMS with regards to hearing in a group of 16 children and young adults (17.3 ± 4.9 years) with and without brain injury. Methods: Pure-tone hearing thresholds and distortion-product otoacoustic emissions were measured before and after exposure to single- and paired-pulse TMS (1–2 sessions of 149–446 TMS pulses at a median of 49%–100% maximum stimulator output over a 2.2 hours period). Results: No mean change in hearing outcomes was noted. In addition, no clinically significant change in hearing threshold was observed in any participant, and participants did not experience a subjective change in hearing after TMS exposure. Conclusions: Single- and double-pulse TMS administered within the parameters used in this study, which included hearing protection, can be used in children and young adults without impacting hearing. This study provides further evidence for hearing safety after TMS exposure in children and young adults.